Connection stiffness identification of historic timber buildings using Temperature-based sensitivity analysis. (15th January 2017) - Lyu, Mengning; Zhu, Xinqun; Yang, Qingshan
Highlights: A novel damage detection method using the temperature-based response sensitivity. Identified the connection stiffness of 'Que-Ti' in historical Tibetan timber buildings. Numerical simulations and field monitoring data have been used to verify the method. Abstract: The beam-column connection, called 'Que Ti', is the key component of historic Tibetan timber buildings to transfer shear, compression and bending loads from one structural element to another. This kind of connections can reduce the internal forces and improve the structure's ability to resist earthquakes. Its structure is very complicated and there is little information about the behaviour of this kind of semi-rigid connections. In this paper, a temperature-based response sensitivity method is proposed to identify the connection stiffness of the 'Que-Ti' in typical historical Tibetan buildings from temperature and strain response measurements. The semi-rigid connection is modeled as two rotational springs and one compressive spring. The temperature is treated as a measurable input and the thermal loading on the structure can be determined from the temperature variation. The numerical results show the method is effective and reliable to identify both unknown boundary conditions and the connection stiffness of the structure accurately even with 10% noise in measurements. A long-term monitoring system has also been installed in a typical historical Tibetan building and the monitoring data are used to further verify the proposed method. The experimental results show that the identified stiffnesses by the proposed method are consistent with that by finite element model updating from ambient vibration measurements.